Computerized Inventory System: An Evaluation of Technology Acceptance Model on Performance of Agricultural Firms in Nigeria - KEHINDE Busola E.; OGUNNAIKE Olaleke O.; ADEGBUYI Omotayo A.; ILOGHO Simon O.; SALAU Odunayo P.; ATOLAGBE Tolulope M.; ADEDUGBA Adebayo T. (Communications of International Proceedings, 2021)
Rapid developments in technology has drastically changed the working and business environment of the agriculture industry. The purpose of this study is to evaluate the Technology Acceptance Model to explain performance of farmers in the agricultural sector of Nigeria. This study evaluates the attitudinal components of perceived usefulness and perceived ease of use on the adoption of technology by local farmers in the western part of Nigeria. The study contributes to knowledge by employing the use of survey research and simple random sampling technique to collect data from 325 local famers. The results of the regression analysis shows that the components of this model has an effect on attitude towards use and intention to use the technology, thus affecting the farmer’s overall performance.  The results of this study is useful not only to farmers but also   manufacturers and managers for effective performance.